An Exploratory Study of the Functional and Intangible Factors in Decisions to Use Service Areas Attached to Motorways - Takuji Takemoto; Tomohiro Honda; Syoma Kiyomitsu; Takuto Takayanagi; Yusuke Tonogaki; Kazuki Yamada; Ryota Yamamoto; Katsunobu Okamoto; Hirioko Oe (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
The purpose of this study is to model the decision-making of users of service areas (SAs) attached to expressways in Fukui Prefecture and to propose a useful scale for understanding actual usage. The data used in the analysis are the results of a questionnaire survey conducted jointly by Central Nippon Expressway Company Limited (NEXCO Central Japan) and the University of Fukui on users from October 2021 to March 2022. NEXCO Central Japan is a company that manages and operates motorways and expressways in Central Japan. Resting facilities on motorways are often referred to as SAs, and many are operated by the NEXCO Central Japan corporate group.